2012
DOI: 10.4145/jahs.42.119
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological cycle in relation to permafrost environment in forest-grassland ecotone in Mongolia

Abstract: In the mountainous regions of northern Mongolia, there are peculiar different patches of the landscape "ecotone" with north-facing forest slope and south-facing grassland slope. The slopes are distinguished as marked contrast of permafrost distribution as well. The present study revealed ecohydrological processes in terms of evapotranspiration and water balance based on continuous observation since 2004 in the ecotone area of Shiljiree river watershed, upper part of Tuul River in Khentii Mountains. Soil moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…The strong reduction in the amount of downward shortwave radiation on the forest floor (Figure ) is related to its modulation by the evolution of forest canopy and the slope, and is one of the factors that reduced ground surface temperatures in summer in the forested areas compared to the steppe (Figure a). The seasonal evolution of the forest canopy in north central Mongolia has been illustrated in other studies (Iijima et al ., ; Miyazaki et al ., ), where it has been observed that leaves emerge in May, mature in July and die in mid‐September. Permafrost beneath forested north‐facing slopes is impermeable to groundwater flow (Ishikawa et al ., ), and it reduces evapotranspiration from this slope (Iijima et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The strong reduction in the amount of downward shortwave radiation on the forest floor (Figure ) is related to its modulation by the evolution of forest canopy and the slope, and is one of the factors that reduced ground surface temperatures in summer in the forested areas compared to the steppe (Figure a). The seasonal evolution of the forest canopy in north central Mongolia has been illustrated in other studies (Iijima et al ., ; Miyazaki et al ., ), where it has been observed that leaves emerge in May, mature in July and die in mid‐September. Permafrost beneath forested north‐facing slopes is impermeable to groundwater flow (Ishikawa et al ., ), and it reduces evapotranspiration from this slope (Iijima et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The seasonal evolution of the forest canopy in north central Mongolia has been illustrated in other studies (Iijima et al ., ; Miyazaki et al ., ), where it has been observed that leaves emerge in May, mature in July and die in mid‐September. Permafrost beneath forested north‐facing slopes is impermeable to groundwater flow (Ishikawa et al ., ), and it reduces evapotranspiration from this slope (Iijima et al ., ). This results in wet ground at FN (Figure a), which generally has a higher thermal conductivity than dry soils (Farouki, ; Hinzman et al ., ) and should therefore contribute to heat transfer from the ground surface to deep soil layers, enabling a warm soil profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Permafrost fulfills a vital role in sustaining local ecosystem services, because near‐surface soils with shallow active layers remain wet despite low annual precipitation (eg, ). The areas with permafrost overlap considerably with forests and are major source of river water …”
Section: Introductionmentioning
confidence: 99%